A Long-Term Study of Alignment Correction Following Proximal Femoral Varus Osteotomy and Pemberton Osteotomy in Children With Legg–Calvé–Perthes Disease and Developmental Dysplasia of the Hip - Liu, Kuei-Yu; Wu, Kuan-Wen; Lee, Chia-Che; Lin, Sheng-Chieh; Kuo, Ken N.; Chang, Jia-Feng; Wang, Ting-Ming (Frontiers in Pediatrics, 2022)
Proximal femoral varus osteotomy (PFVO) is a common procedure performed in children with developmental dysplasia of the hip (DDH) and Legg-Calvé-Perthes disease (LCPD). However, the long-term effect on angular deformities of the knees and ankles following PFVO remains controversial. This study investigated the relationship between PFVO and alignment changes in knee and ankle after the procedure. Twenty-five patients undergoing PFVO procedure with a minimum 4-year evaluation period were enrolled in the study, including 14 unilateral LCPD and 11 unilateral DDH. The standing scanogram examinations were collected before the operation, immediately following surgery, 1-year follow-up, 3-year follow-up and the final visit to the clinic. The radiographic parameters included leg length, femoral neck-shaft angle (FNSA), femorotibial angle (FTA), mechanical axis deviation (MAD), tibiotalar angle (TTA), and mechanical lateral distal femoral angle (mLDFA). At the final examination, FNSA demonstrated insignificant change between the operative and non-operative limbs in DDH group. Compared with the post-operative result, FNSA significantly improved in LCPD group (p = 0.039). Both groups did not develop statistical significance in TTA, mLDFA, MAD, and leg length discrepancy after more than 5-year follow-up. From a biomechanical perspective that the foot passes more medial to the knee under the center of leg mass, varus knee was prone to develop. In order to correct the mechanical axis, it reverted to a valgus position gradually. Our study indicates that patients with LCPD or DDH receiving PFVO and Pemberton osteotomy narrow the gap of angular growth in knees and ankles between the operative and non-operative limbs after a long-term follow-up.